Impact of nutritional intervention on the weight of B40 children in Selangor - Rusli, Mohammad Farhan; Zainal Abidin, Muhammad 'Adil (2022)
Nutritional status is a significant measure of the overall health of the population. Among children of the most vulnerable groups to have malnutrition are those in the B40 group, with Selangor being the most populous state that has these vulnerable populations. This study aims to assess the impact of nutrition intervention in reducing underweight prevalence among children in the Selangor B40 group. The data was collected from June 2022 until October 2022 from 500 children aged 1 to 6 years old. Intervention includes a monthly food pack consisting of specialised formula milk and multivitamins alongside nutrition counselling Monthly weights were taken for 5 months using the SECA weight scale model 874 and it was monitored using the WHO AnthroPlus. The majority of the respondents were male (51.3%). Baseline results showed 20.6% underweight respondents with 14.4% moderately underweight and 6.2% who were severely underweight. Mean weight increment was observed the highest during the fifth month with 1200g, followed by 510g, 450g, and 110g for the fourth, second, and third month, respectively. A declining prevalence of underweight was observed by the fifth month (10.9%) with 9.2% moderately underweight, 1.7% remains severely underweight and 9.7% children progressing to normal weight. By giving nutrient supplementation, it helps to improve the weight of these children. However, other factors that may contribute to undernutrition such as maternal diet, food insecurity, nutrition education and complications from a variety of diseases should not be overlooked.